Pengaruh Kualitas Makanan Terhadap Keputusan Pembelian Ayam El-Polo di Kecamatan Teluk Jambe Timur - Yossy Marsyatrinisa; Sekar Nirwana Ros Sinta Aji; Abdul Yusuf (Economic Reviews Journal, 2024)
This research was conducted with the aim of analyzing and testing the influence of food quality on purchasing decisions at El-polo Chicken, East Teluk Jambe District. This research was carried out using descriptive and verification methods, namely: collecting data, presenting, analyzing and testing hypotheses, as well as making conclusions and suggestions. The sample in this study consisted of 100 respondents, including students from Singaperbangsa University and native Karawang consumers of El-polo Chicken. The sampling technique used in this research is non-probability sampling, in the form of accidental sampling where the researcher can assign samples to anyone the researcher meets. The analysis used in this research is simple regression analysis, where changes in variable X will be followed by changes in variable Y. The tool used in this research is SPSS software. The results of this research are that, partially, food quality has an influence on purchasing decisions.